Catalytic effectiveness of porous particles: A continuum analytic model including internal and external surfaces. (20th July 2017) - Cohen, Dror; Merchuk, Jose; Zeiri, Yehuda; Sadot, Oren
Graphical abstract: Highlights: Pseudo-continuum analytic model explicitly including external and internal surfaces. Correct description of nonporous and highly porous limits. Influence of external surface on catalytic effectiveness derived and explained. Abstract: The well-known pseudo-continuum model of porous catalysts was based on the generally realized assumption that the external surface of the particle is negligible compared to the internal one. While valid for most industrial applications, this assumption may be inapplicable in some cases, especially for micro- to nano-catalytic particles and low internal surface cases. Herein, we developed a descriptive analytic model that explicitly accounts for both the internal and external surfaces. The model correctly describes the two limiting cases of non-porous and highly porous materials. Moreover, we show that by accounting for the external surface, the present model produces substantially different estimation of the catalytic effectiveness compared to that achieved with the traditional pseudo-continuum model.